Clinical outcomes of Carbomedics Top Hat valve with a robust follow-up system. (January 2015) - Senanayake, Eshan L; Howell, Neil J; Pagano, Domenico; Ray, Daniel; Mascaro, Jorge; Rooney, Stephen J; Wilson, Ian C; Graham, Tim R
Aim: Late failure of bioprosthetic valves may limit their use in patients < 60 years. The superior hemodynamic performance offered by the Carbomedics Top Hat supraannular valve enables greater effective orifice areas to be achieved. The aim of this study was to assess the clinical outcomes of this valve, using a robust follow-up system. Methods: Patients who underwent aortic valve replacement with or without coronary artery bypass grafting between July 1997 and January 2010 with Carbomedics supraannular Top Hat valves were identified. Details of readmissions and late deaths were obtained from the National Hospital Episodes Statistics data and the Office of National Statistics, tracked by the Quality and Outcomes Research Unit. Late complications associated with this prosthesis were evaluated. Results: Of 253 patients identified, 181 underwent isolated aortic valve replacement and 72 had aortic valve replacement with coronary artery bypass grafting. The 30-day mortality was 1.6%, and 5- and 10-year survival rates were 91.4% and 80.5%, respectively. Detailed readmission data were available after 2001 ( n  = 170). Two (1.2%) patients required reoperation for endocarditis and pannus formation. Of the 17 late deaths in this subset, 4 were attributable to cardiac causes. One patient was treated for heart failure, and 2 developed bleeding complications. Conclusions: Implantation of the Carbomedics Top Hat supraannular valve in our unit resulted in satisfactory in-hospital and midterm survival with low incidences of endocarditis and late heart failure.